Hepatic IFNL4 expression is associated with non‐response to interferon‐based therapy through the regulation of basal interferon‐stimulated gene expression in chronic hepatitis C patients. Issue 7 (27th February 2017) - Murakawa, Miyako; Asahina, Yasuhiro; Kawai‐Kitahata, Fukiko; Nakagawa, Mina; Nitta, Sayuri; Otani, Satoshi; Nagata, Hiroko; Kaneko, Shun; Asano, Yu; Tsunoda, Tomoyuki; Miyoshi, Masato; Itsui, Yasuhiro; et al.
Abstract : Single nucleotide polymorphisms (SNPs) within or near interferon lambda 4 ( IFNL4 ) gene located upstream of IFNL3 are associated with response to anti‐HCV therapy both in interferon (IFN)‐based and IFN‐free regimens. IFNL4 encodes IFNλ4, a newly discovered type III IFN, and its expression is controlled by rs368234815‐TT/ΔG, which is in strong linkage disequilibrium (LD) with other tag SNPs within or near IFNL4 such as rs12979860 and rs8099917. Intrahepatic expression levels of IFN‐stimulated genes (ISGs) affect the responsiveness to IFNα and are also associated with IFNL4 genotype. However, IFNL4 expressions and its role in intrinsic antiviral innate immunity remain unclear. This study evaluated the effect of IFNL4 on intrahepatic ISG expression and investigated its relationship with treatment outcomes in liver samples obtained from 49 chronic hepatitis C patients treated with pegylated (PEG)‐IFN/ribavirin therapy. IFNL4 mRNA was detected in 11 of 22 patients with IFNL4 ‐unfavorable SNPs but not in patients with favorable genotypes. IFNL4 expression was associated with non‐response to PEG‐IFN/ribavirin therapy. Intrahepatic expression of antiviral ISGs ( ISG15 and MX1 ) was significantly higher in IFNL4 ‐unfavorable patients with detectable IFNL4 mRNA than in patients with undetectable IFNL4 mRNA, whereas the expression of suppressive ISGs ( RNF125, SOCS1, SOCS3, and RNF11 ) was lower in patients with detectable IFNL4 mRNA. In summary, intrahepatic expression of IFNL4 was associated with increased antiviral ISG expression and decreased suppressive ISG expression at baseline, resulting in poor responsiveness to IFNα‐based therapy in HCV infection.